DIVORCE IN ALBANIA AND THE PROBLEMS THAT IT CARRIES - Alketa Molla (European Scientific Journal, ESJ, 2015)
Divorce is a current problem and a common concern in our society today. In Albania, divorce has become a common thing. Many new couples go for divorce, and not only couples in their first few years of marriage. Divorce basically results from the problems couple encounters in their relationship. These problems are caused by external factors which act indirectly on the couple's relationship. Here, we can mention factors such as the difference in the age of the partners, educational level, residing in part of the urban or rural areas, social and economic conditions of the couple, living sites of partners, and their parent’s interference. The interior factors involve displaying love and support during the marriage. In addition, the level of recognition they have for each other before marrying is a very important factor. Also, their emotional state of feelings and affections they have for each other is also an important factor to be put into consideration. In this article, we will treat at length the problems associated with divorce by analyzing each of them. The study was conducted in the region of Elbasan. Study data were obtained from the Court of Elbasan, as well as NGO "Women's Forum Elbasan." A portion of the data was obtained from the interviews conducted with partners who have requested for a divorce.